2016 Comprehensive Update of the Banff Working Group on Liver Allograft Pathology: Introduction of Antibody‐Mediated Rejection. Issue 10 (14th July 2016) - Demetris, A. J.; Bellamy, C.; Hübscher, S. G.; O'Leary, J.; Randhawa, P. S.; Feng, S.; Neil, D.; Colvin, R. B.; McCaughan, G.; Fung, J. J.; Del Bello, A.; Reinholt, F. P.; et al.
Abstract : The Banff Working Group on Liver Allograft Pathology reviewed and discussed literature evidence regarding antibody‐mediated liver allograft rejection at the 11th (Paris, France, June 5–10, 2011), 12th (Comandatuba, Brazil, August 19–23, 2013), and 13th (Vancouver, British Columbia, Canada, October 5–10, 2015) meetings of the Banff Conference on Allograft Pathology. Discussion continued online. The primary goal was to introduce guidelines and consensus criteria for the diagnosis of liver allograft antibody‐mediated rejection and provide a comprehensive update of all Banff Schema recommendations. Included are new recommendations for complement component 4d tissue staining and interpretation, staging liver allograft fibrosis, and findings related to immunosuppression minimization. In an effort to create a single reference document, previous unchanged criteria are also included. Abstract : The Banff Working Group comprehensively updates guidelines for liver allograft pathology on the basis of pertinent literature, data review, and discussion over the last 5 years. See the editorial from O'Grady onpage 2773 .